Establishment of nuclear transformation protocol of green microalgae Ankistrodesmus convolutus using electroporation - Vu, Thi Quynh Chi (2013)
Despite the availability of some expression systems such as mammalian cell,yeast, bacteria, insect cell, and fungi, green microalgae have risen as interesting alternative systems for the expression of recombinant proteins. The world of algae is tremendously diverse but the number of species exploited for biotechnological applications is quite limited due to the lack of transformation system and molecular information. As a green microalgae,Ankistrodesmus convolutus is a fast growing green microalgae species that contains appreciable amount of carotenoids, polyunsaturated fatty acids and lutein which make this speciesapotential feed in poultry industry. Development of a transformation protocol for this species is essential prior to any of its application for gene manipulation. This study was aimed to establish a nuclear transformation protocol for A. convolutus using electroporation method. The expression vector,pEXP-GUS was created by the modification of pMDC-141 vector. This expressionvectorharbors a β-glucoronidase encoding gene (gusA) and ahygromycin phosphotransferase gene (hpt) conferringhygromycin resistance driven by double CaMV35S promoter. Minimal inhibitory concentration test of hygromycin showed that non-transformed A. convolutus was inhibited at the concentration of 40 mg/L in solid medium after 10 days of inoculation. The parameters of electroporation including cell treatment, electric pulse, concentration of expression vector, concentration of carrier DNA (salmon sperm DNA) and cuvette width were optimized. The results of this study showed that highest transformation efficiency of A. convolutus was obtained when usingcells treated with cellulase (2%) and pectinase (0.3%) before transformation and electric pulse of 1800 V. The optimal concentrations of the expression vector and carrier DNA were10 μg/mL and 50 μg/mL, respectively. Electroporation cuvette with 4 mm gap was more efficient than the 2 mm gap cuvette in introducing foreign gene into A. convolutus. The highest transformation efficiency was 481 transformants per μg DNA use and the transformation yield was 48 x 10-6 cells. A total of 14 transformants were obtained after six rounds of subculturing. The presence of transgenes including hpt gene and gusA gene were then analyzed by PCR and Southern blot analysis. The resultsrevealed the presence of both hpt gene and gusA gene in three transformants namely AcG3, AcG4, AcG14. Among these three A. convolutus transformants, only one transformants gave hybridization signal when the XbaI-digested genomic DNA of PCR-positive transformants was hybridized to a biotin-labelled gusA gene specific probe. This result implied the integration of gusA into the genomes of the transformed cells. The present study was successful in introducing the foreign genes into A. convolutus using electroporation. Hence,this success facilitates the expression of foreign genes in this algae species. It is now feasible to exploit A. convolutus as an alternative system for the expression of recombinant proteins. Particularly, the prospective of using transgenic A. convolutus as oral vaccine or source of recombinant lutein for poultry can be examined.